2019
DOI: 10.35654/ijnhs.v2i2.95
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to pasung on people with mental illness

Abstract: Physical restraint and confinement (pasung) by families of people with mental illness is known to occur in many parts of the world Pasung is a common human right violation on people with mental illness found on every country in the world especially in developing countries like Indonesia. In Indonesia the term pasung refers to the physical restraint or confinement of "criminals, crazy and dangerously aggressive people. Despite the classification as Human Right Violation, pasung is constantly performed in Indone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 7 publications
1
17
0
1
Order By: Relevance
“…That is, responses to the instrument are consistent and are reliable measures of the level of intention of the mentally ill patient’s family to use pasung 8 Dewi et al (2019) [ 32 ] The study demonstrated that family burden was significantly lower among those who received the combination of the two therapies (family psychoeducation and care decisions without pasung) compared to only family psychoeducation (p < .05). Those therapies decreased the family burden into the low category 9 Eka and Daulima (2019) [ 33 ] Ten studies were found. There were 3 main factors related to pasung: 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, responses to the instrument are consistent and are reliable measures of the level of intention of the mentally ill patient’s family to use pasung 8 Dewi et al (2019) [ 32 ] The study demonstrated that family burden was significantly lower among those who received the combination of the two therapies (family psychoeducation and care decisions without pasung) compared to only family psychoeducation (p < .05). Those therapies decreased the family burden into the low category 9 Eka and Daulima (2019) [ 33 ] Ten studies were found. There were 3 main factors related to pasung: 1.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies reported that myths and beliefs in the general population about mental disorders are associated with the increased use of pasung [6,7,33,35,36,42,49,51,57,58]. PWMD are often considered dangerous and/ or possessed by demons.…”
Section: Communitymentioning
confidence: 99%
“… 2 Also, community factors such as discrimination and stigma play an important role in the idea of pasung to patients with schizophrenia. 3 …”
Section: Introductionmentioning
confidence: 99%
“…The reported studies included different subjects of the research. The family or caregivers of the patients as the subject of the study were reported in 17 studies (puji Lestari zumratil Ch, 2010; Suharto et al , 2014; Suswinarto et al , 2015; Empati et al , 2016; Nihayati et al , 2016; Aprilia Wulan, 2017; Suhron, 2017; Sunarno and Suryani, 2017; Yusuf et al , 2017; Buanasari et al , 2018; Laila et al , 2018; Dewi et al , 2019; Dwijayanti and Dharmawan, 2019; Katuuk et al , 2019; Yunita et al , 2020), the patients in 13 studies (Minas and Diatri, 2008; Puteh et al , 2011; Marthoenis et al , 2012; Rahayu et al , 2016; Tanra and Roosdy, 2017; Achir Yani Syuhaimie Hamid and Catharina Daulima, 2018; Aiyub, 2018; Laila et al , 2018; Novy Helena et al , 2018; Eka and Daulima, 2019; Rokhman et al , 2019), the community in two studies (Suryani et al , 2011; Syarniah et al , 2016), and the mix of family and the patients in two studies (Husmiati, 2016; Fitrikasari, 2012).…”
Section: Resultsmentioning
confidence: 99%